1780 N.J. Laws 42-43 - (:unkn) unknown (My University, 1780)
And Be It Enacted, That the Captain or Commanding Officer of each Company shall keep a true and perfect List or Roll of all effective Men between the Ages of sixteen and fifty Years, residing within the District of such Company . . . And Be It Enacted, That every Person enrolled as aforesaid shall constantly keep himself furnished with a good Musket, well fitted with a Bayonet, a Worm, a Cartridge-Box, twenty-three Rounds of Cartridges sized to his Musket, a Priming Wire, Brush, six Flints, a Knapsack and Canteen, under the Forfeiture of Seven Shillings and Sixpence for Want of a Musket, and One Shilling for Want of any other of the aforesaid Articles, whenever called out to Training or Service . . . Provided always, That if any Person be furnished as aforesaid with a good Rifle-Gun, the Apparatus necessary for the same, and a Tomahawk, it shall be accepted in Lieu of the Musket and the Bayonet and other Articles belonging thereto. Further required that "each Person enrolled?also keep at his Place of Abode one Pound of good merchantable Gunpowder and three Pounds of Ball sized to his Musket or Rifle
Keywords: ARMED FORCES; MILITIAS; REQUIRED POSSESSION